Review article: nonclinical and clinical pharmacology, pharmacokinetics and pharmacodynamics of etrolizumab, an anti‐β7 integrin therapy for inflammatory bowel disease. Issue 11 (30th March 2018) - Tang, M. T.; Keir, M. E.; Erickson, R.; Stefanich, E. G.; Fuh, F. K.; Ramirez‐Montagut, T.; McBride, J. M.; Danilenko, D. M.
Summary: Background: Novel treatments with superior benefit‐risk profiles are needed to improve the long‐term prognosis of patients with inflammatory bowel disease (IBD). Etrolizumab—a monoclonal antibody that specifically targets β7 integrins—is currently under phase III clinical evaluation in IBD. Aim: This review summarises the available pharmacological and pharmacokinetic/pharmacodynamic data for etrolizumab to provide a comprehensive understanding of its mechanism of action (MOA) and pharmacological effects. Methods: Published and internal unpublished data from nonclinical and clinical studies with etrolizumab are reviewed. Results: Etrolizumab exerts its effect via a unique dual MOA that inhibits both leucocyte trafficking to the intestinal mucosa and retention within the intestinal epithelial layer. The gut‐selectivity of etrolizumab results from its specific targeting of the β7 subunit of α4β7 and αEβ7 integrins. Etrolizumab does not bind to α4β1 integrin, which mediates lymphocyte trafficking to tissues including the central nervous system, a characteristic underlying its favourable safety with regard to progressive multifocal leucoencephalopathy. Phase I/II studies in patients with ulcerative colitis (UC) showed linear pharmacokinetics when etrolizumab was administered subcutaneously at 100 mg or higher once every 4 weeks. This dose was sufficient to enable full β7 receptor occupancy in both blood and intestinal tissues of patients with moderate to severe UC. The phase II study results also suggested that patients with elevated intestinal expression of αE integrin may have an increased likelihood of clinical remission in response to etrolizumab treatment. Conclusion: Etrolizumab is a gut‐selective, anti‐β7 integrin monoclonal antibody that may have therapeutic potential for the treatment of IBD.